Yin-yang pair algorithm based on cubic chaos and lens imaging learning - Li, Shuzhi; Wang, Junbin; Deng, Xiaohong (SPIE, 2023)
In order to solve the problem that the Yin-Yang Pair Algorithm (YYPO) tends to converge prematurely and has low convergence accuracy, a Yin-Yang Pair Optimization Algorithm (CYYPO) that combines Cubic chaotic mapping and lens imaging learning strategies is proposed. The algorithm uses Cubic chaotic mapping to initialize the two points of yin and yang, and uses the strategy of lens imaging learning method to design a new forward and reverse search segmentation method, which is tested by CEC2013 standard test function, and the results show that compared with the most basic YYPO and other five intelligent optimization algorithms, CYYPO has higher computational accuracy and more outstanding performance advantages.